Motion reconstruction for optical tomography of trapped objects. (4th March 2020) - Elbau, Peter; Ritsch-Marte, Monika; Scherzer, Otmar; Schmutz, Denise
Abstract: Optical and acoustical trapping has been established as a tool for holding and moving microscopic particles suspended in a liquid in a contact-free and non-invasive manner. Opposed to standard microscopic imaging, where the probe is fixated, this technique allows imaging in a more natural environment. This paper provides a method for estimating the movement of a transparent particle which is maneuvered by tweezers (assuming that the inner structure of the probe is not subject to local movements) by making use of the assumption of a smooth movement in time. The mathematical formulation of the motion estimation leads to an infinitesimal version of the common line technique used in cryogenic electron microscopy single particle imaging to estimate the orientations of the particles in the probe.